If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying N + -4 = 33 Reorder the terms: -4 + N = 33 Solving -4 + N = 33 Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + N = 33 + 4 Combine like terms: -4 + 4 = 0 0 + N = 33 + 4 N = 33 + 4 Combine like terms: 33 + 4 = 37 N = 37 Simplifying N = 37
| 49v^2=9 | | 3[5-(y+2)]= | | ((1)-(3x/5))=2x/5 | | p-6=-6 | | 8.9-3.3g=2.2j+2.3 | | -14p+59=-9(1-6p) | | 34*4x=341 | | (x-4)(x-1)=6 | | 4x+7+3x=35 | | -.75x+4=-.5x-1 | | a+1/8=3/4 | | 36=b^2 | | 37+c+52=180 | | 14t=196 | | (49-30)= | | k-1/3=4/5 | | 1+1=r | | w-12/7=-122 | | 15x-5x^3=0 | | X33/4-7=9 | | 11x-115=3x-11 | | 3(x+1)=4x | | X+4.1=-6.8 | | 9a=225 | | 4+y+5x=0 | | 2-6p=-8-5p | | 6+12+(49-30)+5= | | Y=cot^4(7x^2) | | -d^2=13d | | 4p=280 | | x-(6+3x)=28 | | 2/3x11/2 |